Lakbay Booklat a feasibility study of a bookmobile for farmers of Barangay Soledad and Barangay Liwayway, Santa Rosa, Nueva Ecija - Cariño, Cindy P.; Faderon, Rosalie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
This study aimed at determining if the concept of a model library catering to farmers' information needs who are living in Barangay Soledad and Barangay Liwayway, Santa Rosa, Nueva Ecija is feasible. There were 314 respondents included in the study: 944 farmers living in Barangay Soledad and 104, in Barangay Liwayway. The study focused on the farmers' needs, their need for a mobile library and the constitution of the collection to be housed in the mobile library.
Notwithstanding its limitation, the study succeeded in confirming the fact that majority (86) of the farmers need and want a bookmobile to have a better chance of improving their state of living. Eighty-two percent of the 314 respondents actually said that they are willing to help in the establishment of a bookmobile.
The study revealed that age group and reading interest are related. When age increases, the reading interest increases, but the increase is little and the effect is not that significant; the educational attainment of the farmers varies according to age group. The study also shows that subject matter preferences are very much related to the information needs of the farmers. Although there is evidence that information needs increase with subject matter preference, the effect is not that significant.
Through investigating and analyzing the users' needs, the fact was established that providing a bookmobile library in Barangay Soledad and Barangay Liwayway Santa Rosa, Nueva Ecija, is feasible.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Bookmobiles -- Philippines -- Nueva Ecija; Farmers -- Philippines -- Nueva Ecija